UNIT 15H.3 RNA Structure Analysis of Viruses Using SHAPE. Issue 1 (2nd October 2013) - Burrill, Cecily P.; Andino, Raul
Abstract: Selective 2′ hydroxyl acylation analyzed by primer extension (SHAPE) provides a means to investigate RNA structure with better resolution and higher throughput than has been possible with traditional methods. We present several protocols, which are based on a variety of previously published methods and were adapted and optimized for the analysis of poliovirus RNA in the Andino laboratory. These include methods for nondenaturing RNA extraction, RNA modification and primer extension, and data processing in ShapeFinder. Curr. Protoc. Microbiol . 30:15H.3.1‐15H.3.12. © 2013 by John Wiley & Sons, Inc.